MOBILE APPLICATION STICKINESS DALAM INOVASI PASAR ONLINE LAMONGAN (POL) DI PERUSAHAAN UMUM DAERAH (PERUMDA) PASAR KABUPATEN LAMONGAN - Novan Hanif Darmawan; Eva Hany Fanida (Publika, 2022)
The development of innovation in the public sector must continue to be improved in order to adapt in a dynamic environment, the development of innovation aims to meet the needs of society. Perumda Pasar Lamongan Regency launched Pasar Online Lamongan innovation so that people can sell and shop products online. POL innovation is proof that The Lamongan Regency Market Perumda supports the government in accelerating and expanding digitalization in the region in accordance with Presidential Decree of the Republic of Indonesia Number 3 of 2021. As a result of the pandemic, consumer behavior is changing as today's society prefers to shop online rather than traditional markets. The purpose of this research is to describe POL application innovation through Mobile Application Stickiness. The type of research chosen by researchers is descriptive research with a qualitative approach using observation, interviews, documentation and literature studies in data collection. The results showed that POL innovation is already going well but still needs further development. Furthermore, the control of the application is well designed so that users can easily operate it. Lamongan Regency Market Perumda builds Communication with users to keep users of the application. Furthermore, responssiveness in the application is still not maximal because there are still errors and lag. Then the POL Context was originally just an online store turned into a local marketplace. The efficacy of POL application has provided many benefits in helping merchants and UMKM to sell products online. Finally, the promotion was carried out by The Lamongan Regency Market Perumda to socialize POL to the people of Lamongan Regency. Keywords: Service Innovation, E-Goverment, Mobile Application Stickiness, Pasar Online Lamongan, Marketplace